(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2018)
It is proved in the article that the main common feature of the concepts of sustainable development and the «green» economy is their focus on preserving nature and preventing warming of the climate, as this leads to deterioration of the social conditions of reproduction not only at the present moment, but also in the future. At the same time, the concept of a «green» economy provides for an accelerated transition to the use of renewable energy sources, which could lead to the closure of many enterprises and a significant reduction of jobs in traditional sectors of the economy. It is revealed that the main problem for most countries of the world is the lack of financial resources for the transition to an ecological economy in which there would be no significant unemployment. In addition, the global trend is a gradual increase in carbon tax rates, which is an overwhelming burden for most developing countries. It is proved that carbon tax is one of the main structural elements of the financial mechanism of the combination of sustainable development and the «green» economy, which besides it includes a range of financial incentives and fines (international investments and innovations, «green» tariffs, «warm» loans , «green» bonds, loans from «green» banks, etc.). It has been found that international environmental organizations and developed countries can not yet allocate appropriate funds to less developed countries for their transition to a «green» economy. Therefore, each country is now looking for ways to combine sustainable development with a green economy that does not hurt its development, but often it does not correspond to the international environmental and climate agreements that have been signed. Therefore, the international community must seek financial incentives to comply with these agreements. It has been proved that the form of solving the problems of financing climate projects in developing countries could be the creation of a Joint International Climatic Fund. It is found that in order to provide conditions for sustainable development, it is possible to use global taxes on financial transactions; taxes on export of oil in developed countries; funds of international development banks; carbon charges, for example, from international transport; part of the direct or indirect subsidies for the extraction and consumption of fossil fuels.